2017
DOI: 10.7759/cureus.1024
|View full text |Cite|
|
Sign up to set email alerts
|

Biochemistry in Endeavor Adventure Racers Study (BEARS)

Abstract: Background: Adventure sports events consist of a combination of two or more endurance disciplines, such as orienteering, running, and rock climbing, that range from a day’s to a week’s duration. No studies have examined acute kidney injury (AKI) in adventure sports athletes.Objectives: To describe the prevalence of AKI in participants in the Endeavor Team Challenge, a 30-hour, 40-mile adventure race.Methods: In this prospective observational study, body weights were recorded at race registration. At the finish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In a prospective observational study of 88 participants in a 40 mile adventure race, the average NSAID intake of those with AKI was 374 mg compared with 250 mg of those without. However, as with the double-blind randomised control trial, these results were insignificant 30…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…In a prospective observational study of 88 participants in a 40 mile adventure race, the average NSAID intake of those with AKI was 374 mg compared with 250 mg of those without. However, as with the double-blind randomised control trial, these results were insignificant 30…”
Section: Resultsmentioning
confidence: 82%
“…However, as with the double-blind randomised control trial, these results were insignificant. 30 A retrospective case series of four runners who developed AKI following the Comrade's marathon (89 km) in South Africa found that three runners had ingested NSAIDs during the race, and the other runner consumed an NSAID 1 week before the race, which could indicate a link between NSAID use and AKI. The study also found that all four runners had taken the same anti-cramp electrolyte supplement, which may have been a confounding variable.…”
Section: Electrolyte Balance and Hyponatraemiamentioning
confidence: 99%